Tren Publikasi Penelitian Tentang Kepemimpinan Perempuan di Indonesia Periode 2000-2022: Analisis Bibliometrik - Malihah, Lola (Universitas Batanghari Jambi, 2024)
Women are generally identified with the role of household affairs due to the perception of patriarchal culture, social and religious factors which are often used as the background. However, as time goes by, women's thinking is also developing, this can be seen from the increasing number of women's participation in politics and organizations. Even now women can become leaders like men. The aim of this research is to determine women's leadership in Indonesia from 2000-2022. This research uses a bibliometric approach. Data sourced from Sinta indexed journals totaling 123 studies. The research results show that the development of research trends related to women's leadership has experienced positive growth, especially in the 2018-2022 range